Contribuições da categoria trabalho: o processo de produção do conhecimento na formação da coordenação da ocupação Eliana Silva - Leonardo Debossan de Oliveira (2018)
This masters work aims at seeking for a better understanding of the neighborhood, villages and slums fighting movement coordinators formation procedure midst its struggle for dwelling to the Eliana Silva community located in Jatoba, Belo Horizonte, Minas Gerais.It presents as justification the need for an in-depth study on the coordination formative process observed that the subjects that compose this body perform an important mobilization work in the community with the homeless families and it also contributes to the university studies on the above mentioned question taking into account that academic production on the subject of urban occupations has made considerable progress and has received greater attention since the second decade of the 2000s.For the research development the Marxist and Marxian theoretical references work under the lens of the ontology of the social being were used by the category work and production knowledge through the mediation and dialogue with the authors Karl Marx, György Lukács and Henri Lefebvre. The data collection was made from the documents analysis of the Revolutionary Communist Party, organization that centralizes the movement, and the theses of the MLB itself; of the on site observation in the community Eliana Silva realized in two distinct moments; and interview with the coordinates of the occupation selected by means of an intentional sampling. As a result, it can be observed that the work category presents itself as a founding factor for the process of knowledge production during the subjects coordination formation